Social Cognitive Predictors of Bystander Intervention in Racial Microaggressions Among College Students - Marks, Laura Reid (Race and social problems, 2024)
Integrating microintervention strategies and the bystander intervention model, we examined social cognitive predictors (i.e., moral disengagement, empathy, and self-efficacy) of the five steps of the bystander intervention model (i.e., Notice, Interpret, Accept, Know, and Act) to address racial microaggressions in a sample of 452 racially diverse college students. Data were collected using an online survey. Path analyses showed that moral disengagement was significantly and negatively related to each step of the model for White students, but for students of color, it was only significantly negatively associated with Act. Empathy was significantly and positively associated with Interpret, Accept, and Act for White students. For student of color, however, there was a significant and positive association solely between Empathy and Act. For both White students and students of color, self-efficacy was positively associated with Notice, Interpret, Accept, Know, and Act. Finally, race did not significantly moderate any relationships. Strengths, limitations, future directions for research, and implications of the study findings are discussed.